IoT-based intelligent source–load–storage coordination scheme for prosumer campus microgrids - Abdul Muqeet, Hafiz; Shahzad, Muhammad; Shehzad, Moazzam; Akhter, Jumshed; Almohaimeed, Ziyad M.; Akram, Rizwan; Hussain, Muhammad Majid (Frontiers in Energy Research, 2022)
Electrical energy is very necessary for human life in the modern era. The rising energy prices, depletion of fossil fuels, and instability of the grid are alarming situations. So, it needs a smart solution to ensure the balance between pricing and saving natural resources. Some other issues like environmental change, limitations on installation of new transmission lines, reliability concerns, and considering the expansion in distributed energy generation technologies promise the implementation of distributed generation extensively. The integration of two or more energy supplies in a power system is known as distributed energy resource system. In this study, a university campus is taken as a case study to reduce the energy cost while considering the aforementioned issues. The intelligent source–load–storage coordination scheme is proposed to utilize the available renewable energy resources with storage systems. The proposed linear model is solved in MATLAB using the exact method technique considering the economic parameters. The campus microgrid analysis is not addressed considering the Internet-of-Thing (IoT)-based building, especially in the scenario of Pakistan. The results show the efficacy of the proposed model and can be implemented on the existing campus for source–load–storage coordination as an economical solution.